2020
DOI: 10.1007/jhep01(2020)165
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Langevin dynamics via holography

Abstract: In this work, we consider non-linear corrections to the Langevin effective theory of a heavy quark moving through a strongly coupled CFT plasma. In AdS/CFT, this system can be identified with that of a string stretched between the boundary and the horizon of an asymptotically AdS black-brane solution. We compute the Feynman-Vernon influence functional for the heavy quark by evaluating the Nambu-Goto action on a doubled string configuration. This configuration is the linearised solution of the string motion in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(95 citation statements)
references
References 101 publications
(198 reference statements)
7
88
0
Order By: Relevance
“…In this context, we capture in the influence functionals, not only the known dissipative physics contained in response functions, gravitationally encoded in the quasinormal modes, but also at the same time, learn about their interactions with the outgoing Hawking quanta. While earlier works, [33], demonstrated this in the context of a single Brownian particle degree of freedom, the present discussion generalizes this to scalar probes of the black hole environment. We should note that earlier attempts to understand fluctuations of the outgoing Hawking quanta, as for example in [51], where the authors studied an interacting scalar model in an ersatz two-dimensional black hole were plagued by infra-red divergences.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…In this context, we capture in the influence functionals, not only the known dissipative physics contained in response functions, gravitationally encoded in the quasinormal modes, but also at the same time, learn about their interactions with the outgoing Hawking quanta. While earlier works, [33], demonstrated this in the context of a single Brownian particle degree of freedom, the present discussion generalizes this to scalar probes of the black hole environment. We should note that earlier attempts to understand fluctuations of the outgoing Hawking quanta, as for example in [51], where the authors studied an interacting scalar model in an ersatz two-dimensional black hole were plagued by infra-red divergences.…”
Section: Discussionsupporting
confidence: 65%
“…The authors of [31] already demonstrated the efficacy of their prescription by obtaining the quadratic influence functional in a low frequency and momentum expansion for a bulk scalar field in the probe limit. 2 Subsequently, [33] explored how this prescription may be employed to study nonlinear Langevin dynamics of a single particle degree of freedom in quantum mechanics. Their analysis subjected the prescription to the test of dealing with self-interacting fields in the bulk and demonstrated that it continues to give reasonable answers.…”
Section: Jhep07(2020)242mentioning
confidence: 99%
See 3 more Smart Citations